BEDHOL BHAWIKARSU, SERVICE LEARNING PROGRAM IN SMAN 3 OF MALANG AS INDONESIA TOP SCHOOL - Fahmi, M. Khoirul (PROSIDING SENANTIAS: Seminar Nasional Hasil Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study explores how Bedhol Bhawikarsu program gives values for students in SMAN 3 Malang toward future leader and gold generation, that took shelter under education ministry of east java. adopting the qualitative research design, the study presented in this paper ascertained the implementation of Bedhol Bhawikarsu that was integrated with every school program, especially with all stakeholders (teachers) and societies. Because of Bedhol Bhawikarsu, all of aspect in this school was able to connect in best vision and mission that was created by School Principle and leading sector, and able to develop society in every sector. By using the design of Bedhol Bhawikarsu Program, it can create best human being or gold generation for Indonesia who has leadership, integrity and social awareness characteristics. From this values, SMAN 3 Malang became top 10 school in Indonesia and this value can bring stakeholder vision toward global school in internationally outlook.